Synthesis and photophysical properties of N,N′-bis(4-cyanophenyl)-3,4,9,10-perylenebis(dicarboximide) and N,N′-bis(4-cyanophenyl)-1,4,5,8-naphthalenediimide - Uzun, Duygu; Özser, Mustafa E.; Yüney, Kıvanç; Icil, Huriye; Demuth, Martin (Elsevier B.V, 2003)
N,N′-Bis(4-cyanophenyl)-1,4,5,8-naphthalenediimide (CN-NDI) and N,N′-bis(4-cyanophenyl)-3,4,9,10-perylenebis(dicarboximide) (CN-PDI) have been synthesized under special conditions in high yield. The compounds are characterized by UV-Vis, IR, NMR, MS, DSC, TGA and CV measurements. The fluorescence lifetimes, quantum yields and singlet-state energies are presented. CN groups at the phenyl moieties improve the thermal stability of the compounds. The LUMO energy values, −3.91 eV (CN-NDI in solution) and −3.96 eV (CN-NDI and CN-PDI at solid state), are determined by cyclic voltammetry. Whereas CN-NDI shows two reversible (−0.89 and −1.34 V) reduction steps (vs. Fc) in solution, CN-NDI and CN-PDI exhibit only one reversible wave at −0.48 V vs. Ag/AgCl at solid state, assigned to the one-electron reduction. Formation of aggregates shifts the UV absorption spectrum of CN-PDI to shorter wavelengths and its lifetime is measured as 4.6 ns at 580 nm. CN-PDI may be a promising dye for organic solar cells.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: N, N′-Bis(4-cyanophenyl)-3,4,9,10-perylenebis(dicarboximide), N, N′-Bis(4-cyanophenyl)-1,4,5,8-naphthalenediimide; Aggregation, Organic solar cells, Electron transfer reactions; N,N′-Bis(4-cyanophenyl)-3,4,9,10-perylenebis(dicarboximide), N,N′-Bis(4-cyanophenyl)-1,4,5,8-naphthalenediimide; PERYLENE, SOLAR-CELLS, DERIVATIVES, CHEMISTRY, PHYSICAL